Summary of the evidence on responses and adaptations derived from crossfit training. A systematic review. - Alejandro Oliver-López; Adrian García-Valverde; Rafael Sabido (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: The present review aims to describe the state of the scientific evidence that exists about acute and chronic adaptations of CrossFit training. Method: This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement (PRISMA). Original research articles published until 7 June 2020, were searched using five databases. A total of 994 original publications were found. A total of 62 papers matched the inclusion criteria. Results: Short-term effects: CrossFit training results in higher physiological demands than other training modalities. Different work of the day analysed by the studies have shown specific performance demand profiles. Besides psychological and mechanical acute effects have been found after CrossFit sessions. So, the negative moods perception appears to reduce after a CrossFit training session. Long-term effects: maximum oxygen consumption improves after CrossFit programmes, in which experienced athletes seem to achieve a higher gain than recreational athletes. Important changes in body composition have been reported by several studies included in this review. From a psychological perspective, CrossFit practitioners obtain a higher adherence to training than occurs in other training methodologies. Prospects and projects: Specific requirements of every work of the day should be studied for the correct administration to participants. Accumulative fatigue indexes should be explored as an overtraining syndrome in CrossFit athletes because several authors have reported psychological variables related to training addiction. Conclusion: CrossFit-based training drives several physiological changes that could be influenced by the athlete’s expertise. Moreover, this type of training requires a high physiological demand, which is perceived by athletes. Nevertheless, participants achieve adherence to CrossFit regardless of their objectives. In the case of high-performance athletes, addictive exercise behaviours have been identified.